Geometrical product specifications (GPS) - Geometrical tolerancing - Tolerances of form, orientation, location and run-out - International Organization for Standardization
ISO 1101:2017 defines the symbol language for geometrical specification of workpieces and the rules for its interpretation. It provides the foundation for geometrical specification. The illustrations in this document are intended to illustrate how a specification can be fully indicated with visible annotation (including e.g. TEDs). NOTE 1 Other International Standards referenced in Clause 2 and in Tables 3 and 4 provide more detailed information on geometrical tolerancing. NOTE 2 This document gives rules for explicit and direct indications of geometrical specifications. Alternatively, the same specifications can be indicated indirectly in accordance with ISO 16792 by attaching them to a 3D CAD model. In this case, it is possible that some elements of the specification are available through a query function or other interrogation of information on the model instead of being indicated using visible annotation